Effect of mutation on seed coat colour in groundnut (Arachis hypogaea L.) - W. Suradkar*, R. A. Satpute; S. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The seed material of groundnut (Arachis hypogaea L.) variety namely TAG-24, is used in the present study. The mutagenized population showed significantly higher variability in the M2 and M3 generation. Mutation affecting seed coat colour were detected in M3 generation. Highest mutation frequency was induced by15 kR of gamma rays. The seed coat colour mutant showed diverse shades of colour.